2010
DOI: 10.1136/jnnp.2010.212696
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging reveals the role of   activity in eating-reflex seizures

Abstract: In reflex epilepsies, alteration of γ oscillations may mediate transition between interictal and ictal states. Here, we explored a patient having seizures triggered by syrup intake. From intracranial electroencephalography combined with functional MRI, the overlap of the gustatory cortex and of the preictal and ictal onset zones, as defined by early gamma changes, motivated the successful resective surgery of the middle short gyrus of the right insula. This case provides a rare demonstration from human gamma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…Recent studies using spike-triggered EEG-fMRI and ictal single-photon emission CT data in patients with cryptogenic or non-lesional but presumed symptomatic and symptomatic EE with frontal lobe lesions revealed activations over not only fronto-temporo-parietal regions but also occipital and lingual gyri, corresponding to an extensive network [17,10]. fMRI has also demonstrated that limbic systems, including the insula and its connections with the gustatory cortex, are parts of the neuronal networks that process food stimuli [18,19]. Our series also uniquely emphasizes broad epileptogenesis involving the PC in cryptogenic EE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies using spike-triggered EEG-fMRI and ictal single-photon emission CT data in patients with cryptogenic or non-lesional but presumed symptomatic and symptomatic EE with frontal lobe lesions revealed activations over not only fronto-temporo-parietal regions but also occipital and lingual gyri, corresponding to an extensive network [17,10]. fMRI has also demonstrated that limbic systems, including the insula and its connections with the gustatory cortex, are parts of the neuronal networks that process food stimuli [18,19]. Our series also uniquely emphasizes broad epileptogenesis involving the PC in cryptogenic EE.…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to determine the exact ictal onset zone based on surface EEG or functional imaging observations [20] and this applies to all patients with generalized epilepsy syndromes wherein cortical-subcortical interactions have been hypothesised as forerunners of epileptogenesis. One study utilized stereo EEG, taste fMRI, and simultaneous EEG-fMRI in a patient with refractory EE following surgery for right opercular-insular cavernoma, and demonstrated a pre-ictal increase of gamma activity and fMRI activation in the middle insula [19]. This led to successful insular resection.…”
Section: Discussionmentioning
confidence: 98%
“…3B), we could compute the correlation between PET and SEEG data (Fig. 3C), which revealed a significant negative cross-correlation only in the 80-160 Hz frequency band (cc 2-7 = À0.1223, p 2-7 = 0.3738; cc [8][9][10][11][12][13][14][15][16][17][18][19][20] = À0.0472, p 8-20 = 0.7324; cc 80-160 = À0.3081, p 80-160 = 0.0263). The negative value of the correlation indicates that regions showing iHFOs showed a tendency for interictal hypometabolism in this patient.…”
Section: Case Studymentioning
confidence: 99%
“…It is shown as a color scale overlying the magnetic resonance imaging (MRI) of the patient's brain. The epileptogenicity map has good reproducibility and sensitivity and has proved to be helpful to better understand the epileptogenic brain networks subserving different kinds of focal seizures . The map allows for a precise quantitative analysis of the SEEG signals and a direct comparison with other imaging tools, such as FDG‐PET scans.…”
mentioning
confidence: 99%
“…It is possible that the unilateral vagus nerve bilaterally modulates the ascending activity at the brain stem level, after going through the tractussolitarius complex. [4] In addition to all these mechanisms, Blauwblomme et al [11] identified overlaps between the gustatory cortex, involving insular, parietal, and frontal regions, and a frontoinsulo-hippocampal epileptogenic network. This epileptogenic network theory may support the mechanism of EE after frontal meningioma resection in our patient.…”
Section: Discussionmentioning
confidence: 99%